Asuhan Keperawatan Pada Tn.H Dengan Benigna Prostat Hiperplasia Post Operasi Open Prostatectomy Di Ruang Anggrek RSUD Pandan Arang Boyolali - Ujiyanti, Anik, Arina Maliya, S.Kep., M.Si.Med (2015)
Background :BPH Is enlargement of the prostate diseases caused by the aging process, typically experienced by men over 50 years of trying, resulting in obstruction of the bladder neck, can hinder bladder emptying and cause urinary disturbances. Aim of Research:To carry out nursing care on the patient's Prostate Hyperplasia Benigna Post Open Prostatectomy Surgery include assessment, intervention, implementation and evaluation of nursing. Results :After nursing care during 3x24 hours obtained results in diagnosis of pain pain scale results obtained in patients initially reduced 7 to 5, There are no signs of an infection include no redness, the patient is able to do the activities and exercises independently of patients is independent of the whole family and nurses and a patient's sleep needs are met with the results of eye bags are not visible. Conclusion :Diagnoses are presented in cases of prostate Hyperplasia Benigna Post Open Prostatectomy Surgery on Mr. H. Application of nursing care of Prostate Hyperplasia Benigna issue is resolved in part because the diagnosis of pain has not fully lost pain, diagnosis of the risk of infection is not resolved because the catheter still attached, interference physical immobility is not fully resolved because the activities still assisted families, interference of sleep patterns is not resolved because the sleeping patients were disturbed at night. Nursing action plan and most have already applied, and nursing actions followed suit the next program. Keywords :OpenProstatectomy, benignprostatehyperplasia.